2005
DOI: 10.1136/bjsm.2003.011387
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation in the erythropoietic response to altitude training in elite junior swimmers

Abstract: Objectives: Inter-individual variations in sea level performance after altitude training have been attributed, at least in part, to an inter-individual variability in hypoxia induced erythropoiesis. The aim of the present study was to examine whether the variability in the increase in total haemoglobin mass after training at moderate altitude could be predicted by the erythropoietin response after 4 h exposure to normobaric hypoxia at an ambient Po 2 corresponding to the training altitude. Methods: Erythropoie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
86
2
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(109 citation statements)
references
References 27 publications
12
86
2
9
Order By: Relevance
“…The relative increase (compared to non-responders) in the current study in SpO 2 in responders (which corroborates the theory of Chapman et al could be explained in part by increased haemoglobin concentration [30], enhanced erythropoietic response [7,31], which may result in increased red cell volume [4] and subsequently increased arterial oxygen content. Weil et al noted a graded response such that an increase in red cell mass was proportional to oxyhaemoglobin saturation at sea level and altitude [32].…”
Section: Citation: Hamlin Mj Manimmanakorn a Creasy Rh Manimmanakosupporting
confidence: 78%
See 2 more Smart Citations
“…The relative increase (compared to non-responders) in the current study in SpO 2 in responders (which corroborates the theory of Chapman et al could be explained in part by increased haemoglobin concentration [30], enhanced erythropoietic response [7,31], which may result in increased red cell volume [4] and subsequently increased arterial oxygen content. Weil et al noted a graded response such that an increase in red cell mass was proportional to oxyhaemoglobin saturation at sea level and altitude [32].…”
Section: Citation: Hamlin Mj Manimmanakorn a Creasy Rh Manimmanakosupporting
confidence: 78%
“…The mechanisms that contribute to individual variability in responders and non-responders are difficult to elucidate. Large interindividual variations in physiological responses to hypoxia have been reported, including, erythropoietin release [7] and maximum oxygen consumption [5]. Previous research has suggested a possible reason for performance variation with altitude training may be differences in gene expression [11,13] and may also relate to different stress thresholds within athletes [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knaupp et al (1992) Rusko et al (1995); Mattila and Rusko, (1996);Chapman et al (1998);Piehl-Aulin et al (1998); Rusko et al (1999); Ashenden et al (2000); Koistinen et al (2000); StrayGundersen et al (2001);Ge et al (2002);Friedmann et al (2005) Ն3800 m (F IO2 ϳ0.135) Eckardt et al (1989); Knaupp et al Vallier et al (1996);Garcia et (1992); Savourey et al (1996);al. (2000); Katayama et al Rodriguez et al (2000); Niess et al (2003); Julian et al (2004); ( Rusko et al (1995); Mattila and Rusko (1996); Savourey et al (1996); Chapman et al (1998);Piehl-Aulin et al (1998a);Piehl-Aulin et al (1998b); Rusko et al (1999); Ashenden et al (2000); Koistinen et al (2000); Stray-Gundersen et al (2001); Dehnert et al (2002); Ge et al (2002) brecht and Littell, 1972;Eckardt et al, 1989).…”
Section: Introduction Ementioning
confidence: 99%
“…También existen otras investigaciones previas (Calbet et al, 2003;Consolazio, Nelson, Matoush & Hansen, 1996;Wolfel, Groves & Brooks, 1991;Tadibi, Dehnert, Menold & Bartsch, 2007) que utilizan la exposición a hipoxia intermitente como estímulo, donde el umbral anaeróbico no se modificó o incluso descendió trasun programa de altitud simulada (Katayama, Matsuo, Ishida, Mori & Miyamura, 2003;Lundby, Nielsen & Dela, 2005). Los resultados de nuestra investigación son compartidos por Bonetti et al (2009) que observaron un incremento del 6.5% en la potencia generada en el umbral anaeróbico de 18 triatletas y ciclistas después de 15 sesiones de 60 minutos de duración a una SpO2 del 76-90% o por Friedmann et al (2005) que observaron un incremento del 3 % en la velocidad del umbral anaeróbico tras un programa de IHE de 4 horas diarias al 15 % del FiO2 en 16 nadadores. Estos resultados concuerdan con los que obtienen Rodríguez, Ventura y Casas (2000) que observaron un incremento significativo en la potencia desarrollada en el umbral anaeróbico en ciclistas después de tres semanas de exposición a hipoxia intermitente a 5500 m, durante 3 horas, 3 veces por semana.…”
Section: Discussionunclassified